HUBUNGAN ANTARA ASERTIVITAS DAN KEMATANGAN DENGAN KECENDERUNGAN NEUROTIK PADA REMAJA - Widjaja, Pauline Dwiana Chrisma; Wulan, Ratna (Faculty of Psychology, Universitas Gadjah Mada, 1998)
The purpose of this study was to examine the correlations between neuroticness, assertivity, and maturity. It was hypotesized that there were relationships between neuroticness, assertivity and maturity; and there was a negative correlation between neuroticness and assertivity, also there was a negative correlation between neuroticness and maturity. The subjects were 95 male and female students of SMK 7 in Yogyakarta, 15 – 18 years old. Three questionaires were applied to measure neuroticness, assertivity, and maturity. Multiple regression analysis was used as a statisticalmethod. Results of the study showed that there was relationship between neuroticness, assertivity, and maturity (F = 6,88; Ry(1-2) = 0,36; p<0,01); and there were positive correlation between neuroticness and asertivity rx1y = 2,12 (p<0,05), there were positive correlation between neuroticness and maturityrx2y = 0,28 (p<0,05). These two minor hypotheses were failed.